An fMRI Investigation of the Neurocognitive Processing of Measures and Strategic Objectives - Black, Paul W.; Kirwan, C. Brock; Meservy, Thomas O.; Tayler, William B.; Williams, Jeffrey (Management Science, 2024)
A central feature of most organizations is the use of measures to represent key elements of performance across multiple strategic objectives. Prior research demonstrates a tendency for individuals to treat these measures as though they are the higher order strategic objectives the measures were intended to represent as opposed to imperfect representations of those strategic objectives—a phenomenon labeled “surrogation.” We employ an experiment to further understand this phenomenon. In this study, we capture neural activation when processing measures and when processing strategic objectives. We find that, in regions of the brain with greater (less) activation for concrete versus abstract words, brain activation is greater (less) when processing measure phrases versus when processing strategy phrases. We further find evidence that greater brain activity and longer response times are associated with less surrogation. This affirms the notion that increased cognitive involvement can reduce surrogation. This paper was accepted by Ranjani Krishnan, accounting. Funding: This work was supported by Auburn University, Brigham Young University, Utah Valley University, and an IMA Research Foundation grant from the Institute of Management Accountants. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2022.01405 .